Leukemia-cell proliferation and disease progression in patients with early stage chronic lymphocytic leukemia - Murphy, E J; Neuberg, D S; Rassenti, L Z; Hayes, G; Redd, R; Emson, C; Li, K; Brown, J R; Wierda, W G; Turner, S; Greaves, A W; Zent, C S; et al. (Leukemia, 2017)
The clinical course of patients with recently diagnosed early stage chronic lymphocytic leukemia (CLL) is highly variable. We examined the relationship between CLL-cell birth rate and treatment-free survival (TFS) in 97 patients with recently diagnosed, Rai stage 0–II CLL in a blinded, prospective study, using in vivo 2 H 2 O labeling. Birth rates ranged from 0.07 to 1.31% new cells per day. With median follow-up of 4.0 years, 33 subjects (34%) required treatment by NCI criteria. High-birth rate was observed in 44% of subjects and was significantly associated with shorter TFS, unmutated IGHV status and expression of ZAP70 and of CD38. In multivariable modeling considering age, gender, Rai stage, expression of ZAP70 or CD38, IGHV mutation status and FISH cytogenetics, only CLL-cell birth rate and IGHV mutation status met criteria for inclusion. Hazard ratios were 3.51 ( P =0.002) for high-birth rate and 4.93 ( P <0.001) for unmutated IGHV . The association between elevated birth rate and shorter TFS was observed in subjects with either mutated or unmutated IGHV s, and the use of both markers was a better predictor of TFS than either parameter alone. Thus, an increased CLL birth rate in early stage disease is a strong predictor of disease progression and earlier treatment.